Alterations in gut microbiota composition in neurodevelopmental disorders: a systematic review and meta-analysis - Yang, Hua; Wang, Anqi; Yang, Jie; Luo, Rong; Yang, Yue (Frontiers in Microbiology, 2025)
BackgroundNeurodevelopmental disorders (NDDs) have been linked to changes in the gut microbiome, but the exact nature of these alterations is not fully understood. This research seeks to explore the variations in both the diversity and composition of the gut microbiota in individuals diagnosed with NDDs.MethodsWe conducted a systematic literature search up to April 2025. Meta-analyses using STATA 16.0 evaluated alpha diversity, beta diversity, and relative abundance between individuals with NDDs and healthy controls.ResultsNo significant alpha diversity differences were found between NDD and control groups. Beta diversity analysis revealed distinct microbial communities across autism spectrum disorder (ASD), attention-deficit/hyperactivity disorder (ADHD), and tic disorder (TD) subgroups. At the family level, NDDs showed increased Peptostreptococcaceae (SMD = 0.47; 95% CI: 0.05 to 0.90). Genus-level analysis demonstrated reduced Escherichia/Shigella (SMD = −0.39; 95% CI: −0.59 to −0.19) and Roseburia (SMD = −0.39; 95% CI: −0.78 to 0), alongside elevated Eubacterium (SMD = 0.33; 95% CI: 0.20–0.47) in NDDs.ConclusionThis study highlights the complex changes in gut microbiota in NDDs, particularly significant differences at the beta diversity, family, and genus levels. However, the results are constrained by research heterogeneity and small sample sizes. To better elucidate these associations, larger, more standardized studies are required.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, CRD42024585913.